Songs for Cabo Verde : Norberto Tavares's musical visions for a new republic - Hurley-Glowa, Susan Margaret (Eastman/Rochester Studies Ethnomusicology Ser., 2021)
Chronicles the work of Norberto Tavares, a Cabo Verdean musician and humanitarian who served as the conscience of his island nation during the transition from Portuguese colony to democratic republic.